Evaluating Functional and Structural Condition Based Maintenances of Airfield Pavements - Tarefder, R.; Ahmed, M.U.; Rahman, M.M. (Civil Engineering Dimension, 2013)
This study evaluates airfield pavements’ functional- and structural-condition to determine the most economical maintenance method. As a part of the analysis, Pavement Condition Index (PCI) for several runways, taxiways, and aprons has been determined by MicroPAVER. Structural evaluation of airport pavements has been performed by Falling Weight Deflectometer (FWD) test. Evaluation of Layer Moduli and Overlay Design (ELMOD) also determines the required overlay thickness based on the E-values, i.e. FWD data analysis. Damage analysis determines the time of repeated overlay application. In addition, functional parameters have been included to determine the time of functional maintenance. Maintenance and rehabilitation alternatives have been selected to develop different program strategies. Life Cycle Cost Analysis (LCCA) has been performed to determine the maintenance cost. Structural condition based maintenance cost is compared to functional condition based maintenance cost. Comparison shows that structural condition based approach yields cheaper maintenance strategies than functional condition based maintenance approach.